THE STRUGGLES OF A DYSLEXIC CHILD: FAMILY, SOCIETY, AND THEEDUCATION SYSTEM IN TAARE ZAMEEN PAR - Badra, Vishnu; Sheeba .C (International Journal of Research -GRANTHAALAYAH, 2025)
Dyslexia is a learning difference but often considered as an academic disability. Children with this differences are often misunderstood and marginalized. It is still neglected in many regions of the world, mainly where rigid academic infrastructures exist to enforce respect for rote learning. The kids in India carry the cross of learning disabilities that is much heavier because intelligence and educational success are thought of as synonymous, if not inextricably linked, with the approval of that society. Taare Zameen Par (2007) is the epitome of contrasted images in a film directed by Amir Khan that brings to light the struggles children with dyslexia have to endure and exposure to the ills behind the Indian educational system. The film is about the life of Ishaan Awasthi, who is so full of creativity but utterly failing in academics. Ishaan's dyslexia remained an undiagnosed medical condition. His teachers, as well as family, misjudged him, and he was sent away to a very strict boarding school, where instead of healing, his wounds of emotions would augment. Then, came his teacher, Ram Shankar Nikumbh,, understanding Ishaan's problems, employed different teaching methods for his betterment. This paper studies the movie's depiction of the ostracism of children with dyslexia, considering its impact on Ishaan's emotional and psychological well-being, parent pressure, competitiveness of the educational system, and society's misunderstanding of intelligence that the movie points toward are critically studied. Taare Zameen Par presents learning-disabled children facing feelings of inadequacy, low self-esteem, and social isolation from these experiences; in this regard, it accentuates the trauma of the mental trauma on academic measurements that are unattainable and stress bestowed by comparisons to other children. This paper also investigates the implications of the representation of neurodivergence in cinematography. It inspects how animation, music, and color coding are used in the film as visual storytelling techniques to depict Ishaan's inner landscapes and emotional turmoil. The second part discusses Nikumbh as a transformative character in Ishaan's journey who stands against traditional methods and calls for a more inclusive and compassionate approach to learning. The family sphere concerning Ishaan's journey forms another focal point of the paper. His parents, especially his father, represent the societal attitude that awards precedence to academic success over individuality. The film's critique centers on how families dismiss unconventional learning requirements, explaining how parental ignorance and pressure can emotionally hurt the child. This research studies how Ishaan's eventual acceptance by and support from his parents reiterate the need for awareness and early intervention concerning learning disabilities. This paper also situates Taare Zameen Par within contemporary scholarly debates about dyslexia and media representation. It scans some earlier research on the depiction of dyslexia in cinema to gauge the film's contribution to controversies.